Barriers to healthcare access in patients with chronic pain or potential migraine in Japan: a cross-sectional internet survey - Karasawa, Yusuke; Yamaguchi, Keisuke; Nakano, Shogo; Nozawa, Kazutaka; Iseki, Masako (Frontiers in Pain Research, 2023)
Purpose Chronic pain and migraines often go untreated despite patient- and economic-related burdens (e.g., impaired quality of life and productivity). Understanding the reasons for non-treatment is important to enable interventions aimed at improving care-seeking behaviors. However, reports on disease-specific justifications for nontreatment in Japan are limited. We aimed to determine the barriers to healthcare access in untreated patients with chronic pain or migraines. Patients and methods This was a non-interventional, cross-sectional, internet questionnaire survey of patients with chronic pain or migraines. The primary endpoint was to identify the reasons for untreated chronic pain or migraines. Secondary endpoints included factors associated with healthcare access, including patient background, patient-reported outcomes, and awareness of generic or authorized generic drugs (AG). Results We surveyed 1,089 patients with chronic pain [605 (55.6%) untreated] and 932 patients with migraines [695 (74.6%) untreated] in 2021. The main reasons for not seeking treatment for chronic pain was “my pain is tolerable” and for migraine, “I can manage my pain with over-the-counter drugs.” Background factors significantly associated with untreated chronic pain were younger age, less time required to access the nearest medical institution, less pain, higher activities of daily living (ADL) scores, and lower awareness of generic drugs and AG. Among patients with migraine, notable characteristics included being female, having shorter travel times to the nearest medical facility, residing in municipalities with populations under 50,000, experiencing moderate to severe pain, having higher ADL scores, and displaying lower awareness of AG. The AG awareness rate was 2-fold higher in treated patients than in untreated patients. Conclusion Educating patients regarding the risks associated with pain and its underlying causes, availability of inexpensive treatment options, and location of appropriate treatment facilities may increase treatment rates.